A Review of Challenges Faced by Educators and their Ripple Effects on Learners’ Outcomes - Dr. Rahmat Ullah Khan ,; Dr. Arshad Khan,; Dr. Nauman Sadiq,; Dr Salah Uddin, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the challenges affecting educators’ performance and their impact on learners’ outcomes at the secondary level. Drawing on a comprehensive review of existing literature, the paper critically analyzes the difficulties faced by school educators in the Punjab province of Pakistan. The study population consisted of secondary-level educators from government schools and their secondary-level learners in District Rawalpindi. The sample included educators with a minimum of five years of teaching experience and learners from grade 9 in selected schools. The study was conducted in two phases. In Phase 1, an opinionnaire utilizing a five-point Likert scale was used to gather educators’ opinions regarding the challenges they faced. In Phase 2, educators were divided into two groups: those experiencing the most significant challenges and those facing minimal challenges in the teaching-learning process. Subsequently, tests were conducted to assess and compare the academic achievements of the learners taught by each group of educators. The findings revealed that a majority of educators encountered various challenges, including financial difficulties, inadequate medical and healthcare support, low social status, issues related to students and their parents, political interference, frequent transfers, lack of accommodation, teaching in non-native languages, transportation problems, insufficient teacher training, inadequate training aids, limited study materials, frequent syllabus changes, lack of refresher courses, and teacher shortages leading to excessive workloads. These challenges adversely impacted educators’ teaching performance, which in turn negatively influenced students’ learning outcomes at the secondary level. The study recommended that educators should be provided with adequate salaries and associated benefits. They should also receive proper social recognition and support from both the government and society. Other recommendations included ensuring suitable accommodation, a conducive school environment, appropriate teaching aids, and effective teacher training programs. Schools should be free from political interference, and adequate staffing should be ensured to address teacher shortages and prevent excessive workloads. Finally, the study suggested conducting broader research to explore additional aspects of the topic.